Relationship between Moral Distress and Job Satisfaction among Nurses of Tehran University of Medical Sciences Hospitals - Soodabeh Joolaee; Hamid Reza Jalili; Forough Rafii; Fatemeh Hajibabaee; Hamid Haghani (حیات, 2012)
Background & Aim: Moral distress, a major issue in nursing, affects nurses in all healthcare sections. The existence of such distress and its consequent job dissatisfaction may pose a threat to nurses&apos physical and mental health, as well as their quality of life and hinder their accomplishment of individual and social goals. The aim of this study was to determine the relationship between the moral distress and job satisfaction In nurses.